2015
DOI: 10.1002/jsfa.7215
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐irradiated β‐glucan induces immunomodulation and anticancer activity through MAPK and NF‐κB pathways

Abstract: These data indicate that LMBG is important in eliciting antitumor activity through a non-specific immune response and may play a major role as a value-added product in the medical industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In this model, addition of LEM did not result in reduced growth of an already established tumor, but addition of this extract 1 week prior to tumor inoculation did significantly reduce tumor growth. In most studies, β-glucan interventions delayed both the onset of tumor growth [105] as well as the progression of already established tumors (all studies monitored tumor growth, except for one study that looked at cecum weight in colon carcinoma [106], and another study that looked at melanoma mass [107]). Notably, two studies documented in their materials and methods two transplanted cell lines but only reported the immune effects toward one of these cell line [108,109].…”
Section: Supportive Effects Of β-Glucans Toward Adoptive T Cell Theramentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, addition of LEM did not result in reduced growth of an already established tumor, but addition of this extract 1 week prior to tumor inoculation did significantly reduce tumor growth. In most studies, β-glucan interventions delayed both the onset of tumor growth [105] as well as the progression of already established tumors (all studies monitored tumor growth, except for one study that looked at cecum weight in colon carcinoma [106], and another study that looked at melanoma mass [107]). Notably, two studies documented in their materials and methods two transplanted cell lines but only reported the immune effects toward one of these cell line [108,109].…”
Section: Supportive Effects Of β-Glucans Toward Adoptive T Cell Theramentioning
confidence: 99%
“…Various mice studies also investigated the effects of β-glucan intake on subsets of immune cells within TME, blood or other organs. There were 7 out of 16 studies that reported increased IFN-γ production following ex-vivo stimulation of either blood-derived T cells, splenocytes, cells from tumor or immune tissues, following uptake of β-glucans [106][107][108][110][111][112][113]. In the study where cells from GALT showed increased IFN-γ production following ex-vivo stimulation, authors argued that administered WGP β-glucans induced IL-12 and TNF-α production by DCs and stimulated DC migration into the tumor, which resulted in local expansion of T cells [108].…”
Section: Supportive Effects Of β-Glucans Toward Adoptive T Cell Theramentioning
confidence: 99%
“…LPS activates RAW264.7 cell immune response through the NF‐ k B signaling pathway . NF‐ k B is an important transcription factor which regulates the expression of a large number of genes that are critical for the regulation of apoptosis, viral replication and inflammation and that are activated in various autoimmune diseases . Normal state NF‐ k B is a dimer comprised of p65 (RelA) and p50 (NF‐ k BI) and exists in the cytoplasm as an NF‐ k B‐inhibitory k B (I k B) complex .…”
Section: Resultsmentioning
confidence: 99%
“…The nephronprotective effects of Iβ-glucan may be attributed to its immunomodulatory effects. Therefore, the protective effect of Iβ-glucan against DEN toxicity could be attributed to their antioxidant and anti-inflammatory efficacy, especially β-glucan, which had low molecular weight, high solubility and low viscosity (Byun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%